"Do this in remembrance of me": Black Bodies and the Future of Theological Education. Issue 4 (January 2020) - Powery, Luke A.
Slavery was an assault on black humanity, including the black body. Theological education paired with and shaped by slavery embodied the same type of violence through its mission and curriculum, that is, the sanctified erasure of black personhood, Christianity, and scholarship. In light of the relationship of Princeton Theological Seminary and slavery, this article focuses on the implications of this history for the mission and curriculum of theological schools, especially as it pertains to wounded black bodies. The key exploratory question will be, "What would theological education look like if it was reimagined through the lens of these black human wounds?"